Correlation of engineering skills and entrepreneurship literacy towards entrepreneurship opportunities Vocational High School students - Faizal Nurkhalim; Setiadi Cahyono Putro; Hakkun Elmunsyah (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2018)
This research aims to know the relationship between engineering skills simultaneously (X1) and entrepreneurship literacy (X2) towards entrepreneurship opportunities (Y). This research is descriptive correlation research which is ex post facto. The subject in this study are students of class XII electrical engineering program, electric power installation skills competency Vocational High School in Malang amounted to 79 students. Data collection engineering skills variables using the documentation value of practical training, while entrepreneurship literacy variables and perceptions towards entrepreneurship opportunities to use the questionnaire. Data analysis includes descriptive analysis and regression. The results of the research that has been done, the significance F of 0.000 < 0.05 (p. sig = 5.00%). So, it can be concluded that there is a positive and significant relationship simultaneously between entrepreneurship, environmental literacy, and proficiency with the perception towards entrepreneurship opportunities.